2018
DOI: 10.1097/qad.0000000000001683
|View full text |Cite|
|
Sign up to set email alerts
|

Neuropsychological performance in African children with HIV enrolled in a multisite antiretroviral clinical trial

Abstract: Significant cognitive deficits were documented among HIV+ children at school age, even when started on ART at an early age. Earlier HIV treatment, neuropsychological monitoring, and rehabilitative interventions are all needed. Subsequent testing for 2 more years will help further evaluate how HIV infection and exposure affect the developmental trajectory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 45 publications
6
50
0
1
Order By: Relevance
“…The purpose was to assess and compare neuropsychological outcomes in three cohorts of young children (5 to < 11 years): HIV-infected (HIV), HIV-exposed but uninfected (HEU) and HIV-unexposed and uninfected (HU) 23 . HIV-infection and exposure was assumed to be perinatal or during breastfeeding.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose was to assess and compare neuropsychological outcomes in three cohorts of young children (5 to < 11 years): HIV-infected (HIV), HIV-exposed but uninfected (HEU) and HIV-unexposed and uninfected (HU) 23 . HIV-infection and exposure was assumed to be perinatal or during breastfeeding.…”
Section: Methodsmentioning
confidence: 99%
“…The KABC-II is designed for children ages 3-18. It was chosen for its demonstrated reliability and crosscultural functionality, including use in other African countries and pilot testing results of the isiZulu language version in South Africa (Kaufman & Kaufman, 2004;Ajayi et al 2017a;Debeaudrap et al, 2018;Boivin et al, 2018Boivin et al, , 2019.…”
Section: Methodsmentioning
confidence: 99%
“…A number of recent studies have suggested that CHEU may be more likely to experience delay or disability in neurocognitive or language development compared to children who are HIV-unexposed and uninfected (CHUU) (le Roux et al, 2018(le Roux et al, , 2019McHenry et al, 2018;Mukherjee, Devamare, Seth, & Sapra, 2019;Wedderburn et al, 2019;Wu et al, 2018). However, conflicting evidence from methodologically similar studies indicates that developmental scores among CHEU do not differ from those of CHUU (McHenry et al, 2018;Boivin et al, 2018;Desmonde, Goetghebuer, Thorne, & Leroy, 2018;Springer et al, 2018Springer et al, , 2019. Many of the studies to date have been limited by small sample size, differing recruitment and eligibility criteria for the CHEU, CHUU, and CLHIV groups, and/or lack of adjustment for potentially confounding variables, such as household food insecurity or lower education.…”
Section: Introductionmentioning
confidence: 99%
“…[44,45] Since the introduction of paediatric ART, studies have continued to document neurodevelopmental impairment. [46][47][48] Furthermore, there is growing evidence that HEU children may experience early developmental impairment. Previous reviews have reported some delays in cognitive, language or motor development, [47,49,50] although to a lesser extent than in CLHIV and mainly in low-resource settings.…”
Section: Early Neurodevelopmentmentioning
confidence: 99%
“…[46][47][48] Furthermore, there is growing evidence that HEU children may experience early developmental impairment. Previous reviews have reported some delays in cognitive, language or motor development, [47,49,50] although to a lesser extent than in CLHIV and mainly in low-resource settings. [47] A recent study from SA found motor and cognitive delay, particularly associated with preterm birth, [51] and a study from Zambia reported a later impact on school performance.…”
Section: Early Neurodevelopmentmentioning
confidence: 99%